Financial Inclusion Challenges Faced by Rural Micro Businesses in Cuddalore District of India - R. Pazhanisamy (ZBW - Leibniz Information Centre for Economics, 2024)
Small and Micro Enterprises (SMEs) in India are facing many problems such as unable to access to low cost credit from the formal financial institutions, specifically banking and extend their product to the remote markets. Some factors restrict the access to the finance on the input side while others restrict the products and its market outreach on the others side blocks the micro enterprises growth and lead to the rural population to be interlocked in chronic underemployment underdevelopment. With regard to this there are a very few research attempts are only available to test and verify the implication and operations of the Economic theories that highlights these two side issues rationalize how they contribute for the long run credit gap in the rural economy. Particularly the literature on the credit rationing theory on the input side of the financial inclusion policies and the pecking order theory on the demand side of the finance and their inter relationship with other theories like theory of moral hazard, agency theory, and the theory of adverse selection etc. are not documented and tested at the gross root level for which this paper attempted fill this gap.
Keywords: D21; E32; G53; L22; L98; M30; 330; Challenges of Micro Businesses; Issues of Rural Micro Enterprises; Test of theoretical impact on micro businesses; challenges of rural business Management; Financial inclusion challenges in rural areas